Application of the rough set method to the level of customer satisfaction on service quality - Ariwisanto Sianturi, Fricles; Sijabat, Petti Indrayati; Sitohang, Amran (Politeknik Ganesha Medan, 2021)
It is difficult to predict to do a random sampling technique with the consideration that the existing population is very large, so it is not possible to study the existing population. Thus, in the form of a population representative, this research is part of the total customers who stay at Graha Buana Hotel Medan. The decisions taken must consider well based on the data that is held, especially those that are closely related to the hotel service system. The stages of research carried out in research are to conduct interviews by direct questioning to the section related to research, direct observation of events that occur at the research site, analyzing and designing and making applications and testing applications. The Rough Set method is one of the methods above that allows us to make decisions in hotel services because in this method there are formulations or stages of problem mechanics and there is a result (decision) from a possible combination of the above criteria. From the results (decisions) that come from the processed data mining, it can be used as a reference for decision making. The results obtained in this study are finding a rule with the rough set method used to obtain the results of each criterion for service satisfaction results. The results obtained in this study are finding a rule with the rough set method used to obtain the results of each criterion for service satisfaction results.